2017
DOI: 10.1039/c7nj01420a
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of a glucose attached poly(aryl ether) dendron based gel as a drug carrier for a local anaesthetic

Abstract: A poly(aryl ether) dendron based gelator as an efficient transdermal drug carrier for the controlled release of prilocaine hydrochloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Synthesis of a thiolated hyaluronic acid copolymer for drug delivery, EDCI: 1-ethyl-3-(3-dimethyllaminopropyl)carbodiimide hydrochloride, NHS: N-hydroxysuccinimide [137], n represents the number of repeating units. Kannan et al researched the use of a carbohydrate-based low molecular weight gelator 30a (Figure 21) as a drug carrier for a local anesthetic [64]. Compound 30a was found to be capable of entrapping hydrophilic dyes and prilocaine hydrochloride, a local anesthetic drug.…”
Section: Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of a thiolated hyaluronic acid copolymer for drug delivery, EDCI: 1-ethyl-3-(3-dimethyllaminopropyl)carbodiimide hydrochloride, NHS: N-hydroxysuccinimide [137], n represents the number of repeating units. Kannan et al researched the use of a carbohydrate-based low molecular weight gelator 30a (Figure 21) as a drug carrier for a local anesthetic [64]. Compound 30a was found to be capable of entrapping hydrophilic dyes and prilocaine hydrochloride, a local anesthetic drug.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Kannan et al designed and synthesized poly aryl ether and poly alkyl ether glucose cored dendron-based LMWGs ( Figure 21 ) [ 64 ]. The results showed that there is a high tendency for the poly aryl ether dendrons to form strong gel system.…”
Section: Structure and Gelation Properties Of Monosaccharide Derivmentioning
confidence: 99%
See 1 more Smart Citation
“…Marcos et al formulated a poloxamer-hydroxyethyl cellulose-α-cyclodextrin supramolecular gel in water, which sustained a release of the anti-fungal drug griseofulvin for at least three weeks and demonstrated biocompatibility [99]. To deliver a local anesthetic, prilocaine hydrochloride was loaded into a poly(aryl ether) dendron-based gel in DMSO-water solutions by Kannan et al for localized, sustained release [100].…”
Section: Supramolecular Gels For Biomedical Applicationsmentioning
confidence: 99%
“…Glucose derived poly(arylether) dendritic molecules ( 39a–c , Figure 28), exhibit gelation ability; 39b and 39c congeal DMSO and 39a gels in aqueous DMSO (1:1) [122]. The gels have been characterized by SEM, TEM, and PXRD of the xerogel, and also by rheological experiments.…”
Section: Applicationsmentioning
confidence: 99%